2020
DOI: 10.2174/1573403x16666200511085304
|View full text |Cite
|
Sign up to set email alerts
|

Association between Omentin-1 and Coronary Artery Disease: Pathogenesis and Clinical Research

Abstract: : Like other adipokines, omentin-1 is secreted from visceral adipose tissue and plays a vital role in the development of chronic inflammatory diseases, including cardiovascular events. Recent studies have shown that circulating omentin-1 levels are associated with various metabolic risk factors, such as high blood pressure, increased waist circumference, dyslipidemia, and glucose intolerance. The decrease in serum omentin level is an independent predictor of coronary artery disease (CAD) and is associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…Omentin-1 may be protective and proinflammatory cytokines. Additionally, omentin-1 may be related to lipid metabolism (6,11,13) . But Shazia et al (28) said "ACS has no association with LDL-C and T Chol levels".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Omentin-1 may be protective and proinflammatory cytokines. Additionally, omentin-1 may be related to lipid metabolism (6,11,13) . But Shazia et al (28) said "ACS has no association with LDL-C and T Chol levels".…”
Section: Discussionmentioning
confidence: 99%
“…Stejskal et al (30) stated that omentin-1 seems to be a useful biomarker of coronary artery disease across the whole age spectrum. Omentin-1 might be involved in the development of CAD via dysfunction of endothelium dependent coronary dilatation, insulin activity and inflammation (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Omentin-1 activates the Akt signaling pathway, thus, regulating downstream glucose metabolism and could be beneficial for enhancing insulin-stimulated glucose uptake; decreased serum omentin-1 is also associated with inflammatory bowel disease [ 39 ]. Importantly, omentin-1 has been shown to act against atherosclerosis and ischemia-induced revascularization, improve heart damage and functions after reperfusion therapy in patients with acute myocardial infarction, ameliorate acute ischemic injury and stroke, attenuated neointimal formation after arterial injury, and suppressed vascular smooth muscle cells [ 40 , 41 ].…”
Section: Klf2 As the Main Regulator Of The No Productionmentioning
confidence: 99%
“…In his study, Saely et al state that patients within the high omentin group reported significantly more cardiovascular events than patients in the low omentin group [7]. Askin et al stated that a decrease in the omentin levels is an important predictor of CAD and its severity [8]. Zhou et al also found a correlation between higher plasma omentin-1 level and better coronary collateral circulation development [9].…”
Section: Introductionmentioning
confidence: 97%